Perceptions and Health Behaviors of Hypertensive Patients at the Phichit Hospital’s 12 Primary Care Units - Wichianson, Jatturong; Muangphourn, Praphasiri (Journal of Health Science of Thailand, 2018)
The prospective empirical research was conducted to assess perceptions of hypertension and health behaviors in a group of hypertensive patients, and to test the associations among these variables. A total of 496 patients seeking treatment at 12 primary care units within the healthcare network of the Phichit Hospital were asked to complete an anonymous pencil and paper survey between March and May 2008. Surveys contained items measuring demographic variables, perceptions of hypertension, and health behaviors. Results indicate a significant number of participants with low perceptions of health behavioral modifications to control hypertension 36.6 percent, severity of hypertension 31.6 percent, and risk factors associated with blood pressure elevation 23.2 percent. Participants needed most improvement with their diets 40.0 percent, their ability to cope with stress 23.2 percent, and their social relationships 18.0 percent. Results of linear regression indicated significant positive associations between perceived severity of hypertension and compliance with medication (p < 0.01), between social relationships and coping with stress (p < 0.01), and between social relationships and seeking medical attention ( p < 0.01). Present findings provide useful evidence that may be used in the development of appropriate intervention programs to help manage hypertension in similar patient populations.